Гарантування безпеки людини і суспільства як функція держави і монарха у Середньовічній Європі - Загуменна, Ю. О.; Zagumenna, Yu. O.; Юлія Загуменна (Київський часопис права. - 2021. - № 4. - С. 9-18, 2021)
Досліджено, що ключовою політико-правовою підвалиною формування безпекового дискурсу у середньовічній європейській цивілізації була монопольна за своїм офіційним статусом християнська доктрина. Ця доктрина запропонувала цілісне і взаємозумовлене бачення права, держави, суспільства та їхніх зв’язків у встановленні, обґрунтуванні, легітимації і зміцненні засад безпечного існування соціуму. Вона мала внутрішньополітичний і зовнішньополітичний виміри, охоплювала своїм дискурсом взаємовідносини між різними суб’єктами політико-правових відносин, структурувала ці відносини довкола провідних центрів влади, якими у середньовічній Європі були монархічні, феодальні (великі територіальні магнати) і церковні (папство, єпископат) структури, а також сприяла інтегруванню середньовічних суспільств. Показано, що у добу Середньовіччя як цивілізації військово-релігійного типу на першому плані були такі сфери публічної безпеки, як воєнна та релігійна. З’ясовано, що політико-правова думка доби Середньовіччя значно змістила акценти у структуруванні суб’єктів гарантування публічної безпеки, поставивши на перше місце Бога і Церкву як Його земне втілення.

The author shows that the key political and legal basis for the formation of security discourse in medieval European civilization was a monopoly on its official status Christian doctrine. This doctrine offered a holistic and interdependent vision of law, the state, society and their links in establishing, justifying, legitimizing and strengthening the principles of safe existence of society. It had domestic and foreign policy dimensions, covered with its discourse the relationship between the various subjects of political and legal relations, structured these relations around the leading centers of power, which in medieval Europe were monarchical, feudal (large territorial magnates) and church structures. ), as well as contributed to the integration of medieval societies, especially in the stages of decay and decline of the institutions of central government. This concept was largely based on the synthesis of late antiquity political and legal heritage (the idea of the common good, justice, peace, etc.) with the spiritual foundations of Christian doctrine (peace, harmony, order, ideas of godliness, obedience to the law, etc.). It is shown that, being a civilization of military-religious type, the Middle Ages brought to the fore such spheres of public security as military and religious security. It has been found that the political and legal thought of the Middle Ages significantly shifted the emphasis in structuring the subjects of guaranteeing public safety, bringing God and the Church as His earthly incarnation in the first place. Legal institutionalization of public safety was understood in political and legal thought as a complex and dynamic phenomenon, inseparable from the co-creation of God and man: being the ultimate highest authority for guaranteeing public safety, the guarantor of its high axiological value, God nevertheless making one's own efforts to consciously guarantee public safety, along with other social values such as life, justice, equality before God, responsibility, conscience, etc. The weakness of the implementation of the security function by the state and the central government was compensated by the authority and power of the Church, which assumes the security function as the embodiment of God's Will and the prototype of the City of God on earth.

Исследовано, что ключевой политико-правовой основой формирования дискурса безопасности в средневековой европейской цивилизации была монопольная по своему официальному статусу христианская доктрина. Эта доктрина предложила целостное и взаимообусловленное видение права, государства, общества и их связей в установлении, обосновании, легитимации и укреплении основ безопасного существования социума. Она имела внутриполитическое и внешнеполитическое измерения, охватывала своим дискурсом взаимоотношения между разными субъектами политико-правовых отношений, структурировала эти отношения вокруг ведущих центров власти, которыми в средневековой Европе были монархические, феодальные (крупные территориальные магнаты) и церковные (папство, епископство) структуры , а также способствовала интегрированию средневековых обществ. Показано, что в эпоху Средневековья как цивилизации военно-религиозного типа на первом плане были такие сферы публичной безопасности, как военная и религиозная. Выяснено, что политико-правовая мысль эпохи Средневековья значительно сместила акценты в структурировании субъектов обеспечения публичной безопасности, поставив во главу угла Бога и Церковь как Его земное воплощение.
Guaranteeing safety to human beings and society as the function of a state and sovereign ruler in the medieval period of Europe
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; історичний аспект; historical aspect; исторический аспект; Середньовіччя; Middle Ages; Средневековье; держава; state; государство; Бог; God; публічна безпека; public safety; публичная безопасность; монарх; monarch; церква; church; церковь